Association between personality and cognitive bias in adults with and without depression - Bangshan Liu; Mi Wang; Haoting Wang; Yueqi Feng; Yumeng Ju; Jinrong Sun; Xiaowen Lu; Qiangli Dong; Liang Zhang; Ping Wan; Hua Guo; Futao Zhao; et al. (BMC Psychology)
Abstract Background Cognitive bias plays a crucial role in the onset and persistence of depression. Research has established a link between personality traits and cognitive bias; however, most of them focused on the general population, overlooking individuals with depression. We aim to explore the relationship between personality and cognitive bias in patients with major depressive disorder (MDD) and compare the results with healthy controls (HCs) to identify potential patterns. Methods The study included 124 patients with MDD and 123 HCs recruited from the Zhumadian Psychiatric Hospital in Henan, China, using the 16 Personality Factor Questionnaire (16 PF) to measure personality traits and the Cognitive Bias Questionnaire (CBQ) to measure cognitive biases. Pearson correlations and hierarchical regression analyses were employed to investigate the correlations and predictive powers. Results Traits related to neuroticism or extraversion were associated with biased responses. After controlling for sociodemographic and clinical information, neuroticism traits were found to have a significant independent effect in the MDD group. Also, the significance of Privateness in the MDD group merits more extensive exploration. Although consistent correlation patterns were found in both groups, neuroticism traits were more significant and independent in predicting biased cognitive processing in the MDD group, indicating the importance of neuroticism in the depressive context. Conclusions The present study provides insights into the connection between personality and cognitive bias from a clinical perspective, potentially enhancing clinical diagnosis and treatment modalities.